2022
DOI: 10.55544/jrasb.1.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Docking Studies of Some Novel Hetrocyclic Compound as Acat Inhibitors: A Meta Analysis

Abstract: We use molecular modelling and pharmacological testing to identify TCM compounds that may suppress SQS activity. By utilising previously established SQS inhibitors, ten HipHop pharmacophore models were developed. Finally, we used active medicines to explore other potential anti-hyperlipidemia targets in HepG2 cells and establish whether or not the lipid-lowering effect was due to SQS inhibition. As a potential treatment for hyperlipidemia, this research seeks to identify TCM SQS inhibitors. The rings in a hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The vast majority of these activities lead to oxidative stress and the activation of the repair response that is associated with ataxia-telangiectasia mutated/ATM and Rad3-related (ATM/ATR). This response involves the activation of p53 and its subordinate protein p21, which can result in either a stoppage of the cell cycle or an acceleration of the senescence process [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Chemotherapymentioning
confidence: 99%
“…The vast majority of these activities lead to oxidative stress and the activation of the repair response that is associated with ataxia-telangiectasia mutated/ATM and Rad3-related (ATM/ATR). This response involves the activation of p53 and its subordinate protein p21, which can result in either a stoppage of the cell cycle or an acceleration of the senescence process [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Chemotherapymentioning
confidence: 99%
“…The bulk of the hydroxycinnamic acids in hops are composed of caffeine, ferulic acid, and sinapic acid, while the majority of the hydroxybenzoic acids are composed of gallic acid, syringic acid, and vanillic acid [94,95]. The bitter acid equivalents humulone and lupulone are the most prevalent phloroglucinol derivatives found in hops [96,97]. Bitter acids come in two different varieties: humulone-derived -acids and -acids (derived from lupulone).…”
Section: Humulus Lupulus Lmentioning
confidence: 99%
“…[101] Figure 5: Chemical constituents of Ginkgo biloba L G. biloba L. is considered a neuroprotective agent as it possesses antioxidant, anti-inflammatory and vasoregulatory actions and has been proposed in the treatment of glaucoma. [102,103,104] It acts by stabilizing the mitochondria as there are abnormal mitochondrial changes that make the retinal ganglion cells more susceptible to oxidative stress. In a study, it was found that G. biloba L. decreases the level of reactive oxygen species and protects the mitochondrial membrane in cultured neuronal cells.…”
Section: Foeniculum Vulgare Millmentioning
confidence: 99%